2020
DOI: 10.1101/2020.09.29.318865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Nature ofEspeletiaSpecies

Abstract: Species are often regarded as basic units of study in biology, following the presumption that they are real and discrete natural entities. But several biologists wonder if species are arbitrary divisions that do not correspond to discrete natural groups of organisms. Two issues must be addressed to solve this controversy, but few studies seem to do so. The first is whether organisms form sympatric and synchronic groups that are distinct in terms of phenotypes and genome-wide allele frequencies, often called "g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Our findings highlight the need of including specimen-level data in taxonomic descriptions and monographs in the future, and using probabilistic approaches that incorporate the variance and covariance among traits to define species in order to capture the shape of species in nature. Although our results are limited to Escallonia , we speculate this may be a widespread phenomenon in other groups 25 because plant species delimited and described with morphology are rarely based on explicit statistical analyses of phenotypic variation grounded on biological theory 26 , 27 . Therefore, we suggest that investigating the nature of plant species by relying on validating taxonomic species alone can be generally problematic.…”
Section: Resultsmentioning
confidence: 91%
“…Our findings highlight the need of including specimen-level data in taxonomic descriptions and monographs in the future, and using probabilistic approaches that incorporate the variance and covariance among traits to define species in order to capture the shape of species in nature. Although our results are limited to Escallonia , we speculate this may be a widespread phenomenon in other groups 25 because plant species delimited and described with morphology are rarely based on explicit statistical analyses of phenotypic variation grounded on biological theory 26 , 27 . Therefore, we suggest that investigating the nature of plant species by relying on validating taxonomic species alone can be generally problematic.…”
Section: Resultsmentioning
confidence: 91%
“…While our sampling regime emphasizes sympatry, an alternative sampling method is to strive for a large geographic extent with sparsely distributed samples (Stevens, 1997; ter Steege et al ., 2011). In examining the species boundaries of a hypothesized endangered species, however, we argue that it is particularly critical to collect sympatric populations for a more stringent test of the species hypotheses (Pineda et al ., 2020). Sampling sympatric populations may show, as in our study, that phenotypic distinctions in morphological clusters from randomly sample individuals are often narrower than they appear in extant herbarium collections.…”
Section: Discussionmentioning
confidence: 99%
“…Another taxonomic problem is the imperfect concordance between traditional taxonomy and species supported by phenetic or genetic evidence (Cadena et al ., 2018; Pineda et al ., 2020). A previous study found only a c .…”
Section: Introductionmentioning
confidence: 99%